Retos del Derecho constitucional en el Bicentenario de nuestra Independencia - Miranda Bonilla, Haideer (2026)
This paper analyzes some of the main challenges that Costa Rican constitutional law has undergone in the framework of the commemoration of the bicentennial of our independence, such as the constant strengthening of the Constitutional State of Law and our democracy, the protection of human rights of the elderly in the light of active aging, Internet access, the reduction of the digital gap, and effective environmental protection